PEMBERDAYAAN SULTHAN GIFT SHOP MELALUI LITERASI KEUANGAN DAN PENERAPAN TEKNOLOGI INFORMASI DALAM PENGELOLAAN USAHA - Mutiara Lusiana, Annisa; Barovih, Guntoro; Khasanah, Imroatul (UNIVERSITAS SERAMBI MEKKAH, 2025)
This community engagement program was conducted to address several issues faced by Sultah Gift Shop, a small enterprise that continues to experience limitations in financial management and the use of information technology. Initial observations revealed that transaction recording was not performed consistently, basic financial statements had not been prepared, and the use of digital applications in daily operations remained minimal. These conditions made it difficult for the owner to obtain accurate information regarding cash flow, costs, and profitability. In response, the program focused on improving financial literacy and enhancing the use of relevant digital tools to support business management. The implementation stages included field surveys, problem identification, solution development, and the preparation and submission of a proposal to the KPPM of Universitas Internasional Jakarta until approval was granted. The activities involved training on transaction recording, cost calculation, basic financial reporting, and mentoring in using mobile-based financial applications. The results demonstrated an 85% increase in the partner’s financial literacy, the establishment of simple financial reports, and a 90% improvement in the consistency of digital recordkeeping.